Effectiveness of Problem-Based Learning for Improved Learning Outcomes and Critical Thinking - Kurniasih, Enggar; Raharjo, Tri Joko; Yuwono, Agus (Program Magister Pendidikan Matematika, Pascasarjana, Universitas Pasundan in collaboration with Asosiasi Guru Matematika Indonesia (AGMI) and Indonesian Mathematics Educators' Society (IMES), 2024)
Knowing students' learning outcomes and critical thinking abilities is crucial for effective instruction, resource allocation, and improving student learning across various subjects. This encourages testing of the effectiveness of problem-based learning in improving students' learning outcomes and critical thinking abilities. The aim of this research is to describe the impact of implementing the problem-based learning model on improving learning outcomes and critical thinking skills in mathematics learning. This quasi-experimental research employed a pre-test, and post-test control group design involving 42 fifth grade elementary school students in one of the cities in Central Java, with 24 participants assigned to experimental group and 18 participants to control groups. Throughout a four-week duration, the experimental group received instruction utilizing problem-based learning model, while the control group was taught applying traditional learning. Using tests of learning outcomes and critical thinking abilities, both groups were assessed before and after the intervention, and the data were analyzed using descriptive statistics and t-tests. The research findings indicate that problem-based learning has a positive impact on mathematical learning outcomes and critical thinking, with improvements falling within the moderate category. In conclusion, there is a significant difference between classes using the problem-based learning model and conventional classes. This finding enriches our understanding of the effectiveness of innovative teaching methods such as problem-based learning in enhancing learning and critical thinking abilities in the context of mathematics education.